Clinical, Epidemiological, and Oral-Related Factors in Post-COVID-19 Mucormycosis Patients: A Systematic Review of Case Reports - Cano-Verdugo, Guillermo (2025)
Oral mucormycosis has become a significant concern due to increased cases during the COVID-19 pandemic, potentially linked to corticosteroid-induced immune suppression. This study reviews case reports to identify and describe the clinical and epidemiological factors associated with post-COVID-19 mucormycosis from a dental perspective. A comprehensive search of PubMed, Google Scholar, DOAJ, and NIH Library databases yielded 32 relevant case reports from an initial 180. The average age of patients was 53 years, with 21.9% having a confirmed COVID-19 diagnosis one month prior to mucormycosis diagnosis. Corticosteroid use was reported in 65.6% of cases. Common symptoms included pain (65.6%), swelling (21.9%), and ocular pain (12.5%), with Amphotericin B being the predominant treatment (59.4%). Oral manifestations such as maxillary bone exposure (21.9%) and dental abscesses (31.3%) were noted. This study highlights a potential link between corticosteroids and mucormycosis, despite limitations in report consistency and follow-up data, offering valuable insights for clinical management of post-COVID-19 mucormycosis.